Living the forest. The epic as a literary and historiographical discourse of migration and colonization of the Lacandona (Tzintzun, Revista de Estudios Históricos, 2016)
This article explores the process of migration and colonization ofthe Lacandona Jungle through the novel hacia el confin, novela de laselva of Jesús Morales Bermúdez, and also from “El sueño de CarlosHernández” chapter of the book Una tierra para sembrar sueños.Historia reciente de la Selva Lacandona, 1500-200, de Jan de Vos.It analyzes the discursive construction, in narrative terms, of thehistorical process from its representation as epic.
Keywords: historiography; novel; epic; speech; narrative; Lacandona jungle